(untitled) (Journal of Global Accounting, 2024)
This study investigated the influence of forensic accounting skills on fraud investigation in Nigerian electricity distribution firms, with a focus on the Enugu Electricity Distribution Company. A descriptive survey research approach was used in this study. The accountants and whole internal audit personnel of EEDC across the eighteen company’s business districts, as well as the internal audit employees at the company’s corporate headquarters in Enugu, Nigeria, were the subjects of this study. The population of the aforementioned staff members was 52, according to a pilot study. The entire population size of the sampled Enugu Electricity Distribution Company was purposively studied. This is because the population (52) was manageable, and as such, there was no need for sampling. Multiple regression analysis was used to test the hypotheses at a significance level of 5%, and establish the statistical significance of the hypothetical link between the independent and dependent variables. SPSS, Version 20.0, aided this analysis. According to data analysis and regression analysis, The study found that forensic accounting skills of investigative flexibility, accounting and auditing expertise, analytical proficiency, and communication skills have positive and significant impacts on fraud examination in Enugu electricity Distribution Company, Based on the results, Internal Auditors and fraud examiners of the Nigerian electricity distribution companies should be encouraged by the top management and professional bodies to develop more interest on the application of investigative flexibility to enable them carry out effective fraud examination.